ความคิดเห็นของอาสาสมัครสาธารณสุขประจำโรงเรียน (อสร.) ต่อบทบาทในการปฏิบัติงานสาธารณสุขมูลฐานของโรงเรียนและชุมชน จังหวัดนครราชสีมา - วาสนา วรเรียน (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The completeness of physical health and mental health of children and youth are the goal of every countries. Students perception on the importance of primary health care and practice for self health development, involving friends, family and others in community are crucial and benefit in many aspects. The purpose of this cross- sectional descriptive study was to explore the opinion of student health volunteers (SHV) regarding primary health care (PHC) to schools and community in Nakhon Ratchasima province .The importance, real practice, satisfaction and continuing education of a set of key activities indicators specified were determined. The study was conducted during January to February 2003 using self-administered questionnaires with the multi-stage cluster sampling. A total of 710 students from 4th primary to 6th secondary schools from 16 schools 4 zone 4 districts. The majority of respondents were female 57.3%, mean age 12.8 years old, education was primary to secondary 56.6%, mean period of being SHV was 1.6 years and average of students in responsible 1:17 persons. The results indicated that 25 out of 26 activities specified were rated as high important (score 4 and 5) by > 50% of respondents, the top three were advise on self health care, good housing, and promoting exercise. There were only 15 out of 26 activities rated as high practice. For critical success factors listed, 9 activities were marked as high important by >50% and the top three were continuous training, support from all teachers, and schools policy commitment. Further analysis revealed that SHVs in rural setting rated with higher mean scores than SHVs in urban setting statistically significant different (p<0.05) for both the importance and practice of all activities listed, and also more satisfied with those 9 activities specified. Moreover, higher mean scores were found statistically significant different (p<0.05) by dedicated SHV than those forced SHV in all aspects. The result revealed the gaps between the importance and real practice in activities mentioned should be closed through continuous training and support. Students who are willing to be SHV demonstrated more effective performance than those compulsory students.